The role of synergistic interplay among proactive personality, leader creativity expectations, and role clarity in stimulating employee creativity - Wang, Xiaohong; Wang, Meng; Xu, Feng (Frontiers in Psychology, 2022)
This study clarifies the influence of proactive personality on employee creativity by investigating creativity-related expectations in leaders and role clarity in employees. Questionnaires were distributed to obtain 290 leader-employee dyads from China to examine hypotheses via conditional process analysis. Different from our hypothesis, the results show that proactive personality has a positive effect on employee creativity, the leader’s expectations of creativity did not play a significant moderating role on the relationship between proactive personality and employee creativity. The interaction between leader creativity expectations and role clarity has a significant moderating effect on the relationship between proactive personality and employee creativity. These findings are discussed in terms of their theoretical and practical significance.